The development and validation of tour guides internalized occupational stigma scale (TIOSS) - Zhiguang Fan; Xiaoli Shi; Li Liu; Shuhan Yang; Li Li (BMC, 2024)
Abstract Background Tour guides' identification and internalization of occupational stigma may exacerbate their career development, perceived professional reputation and status, and mental health. The current study aimed to develop and verify the Tour guides Internalized Occupational Stigma Scale (TIOSS) to provide an effective tool for relevant quantitative research. Methods The study developed an initial questionnaire through literature analysis, expert review, and semi-structured surveys. We conducted item analyses and exploratory factor analyses among 326 tour guides, and confirmatory factor analysis and reliability and validity tests among 315 tour guides. Results The TIOSS consists of 21 items and is formed in three dimensions referring to Stigma Perception (SP), Status Loss (SL), and Career Denial (CD). The correlation coefficient values of the TIOSS total scale and dimension scores with the criterion instruments ranged from 0.17 to 0.68. In addition, the Cronbach's α coefficients for the TIOSS and its dimensions ranged from 0.837 to 0.928, and the split-half reliability coefficients ranged from 0.843 to 0.916. The study also revealed that the TIOSS was consistent across genders. Conclusion The TIOSS performed favorable reliability and validity to be a valid instrument to assess tour guides' internalized occupational stigma.